Conditioning of the H reflex by stimulation of the posterior tibial nerve in Parkinson's disease. - Martinelli, P (1979)
The excitability curve of the H reflex conditioned by stimulation of a mixed nerve was studied in eight Parkinsonism patients, before and after L-dopa therapy. There was no significant variation between the two curves. However, there was a reduction of the normal early inhibition of the H reflex conditioned by exteroceptive stimulation. This indicates the presence of alterations in the organisation of the reflex pathways at a spinal level in this disease.